Analysis of diaspore morphology and seed germination in Bubon macedonicum L., a rare species in Italy. (4th July 2018) - Di Cecco, V.; Paura, B.; Bufano, A.; Di Santo, P.; Di Martino, L.; Frattaroli, A. R.
Abstract: Bubon macedonicum L. is a chasmophytic species of south-eastern Europe. In Italy, it has been detected only in Rocca Monforte (Campobasso, central Italy). This rare species is included in the IUCN Red Lists of Critically Endangered Italian Flora, and there are no studies relating to B. macedonicum biology. The seed germination dynamics of this species was studied with the aim of building up an appropriate germination protocol to be used in ex situ conservation. On the basis of an ISTA protocol, about 3, 000 seeds were collected from Rocca Monforte in August 2013. Fifty seeds were measured. The considered parameters were seed length, width, thickness, seed surface, volume, density, surface/mass ratio and eccentricity index. The morphometric parameters examined showed morphological dormancy, where a short warm period is necessary for embryo growth and seed germination. The results showed high germination percentages under the different conditions of temperature, pH, GA3 and photoperiod. Only at 5 °C was there no germination. Finally, the seeds maintain high germination percentages from the seed storage process after 130 and 390 days. This factor can be considered of great importance for the conservation of B. macedonicum over the medium and long term.